The effects of an urban renewal project on health and health inequalities: a quasi-experimental study in Barcelona. Issue 9 (6th May 2014) - Mehdipanah, Roshanak; Rodríguez-Sanz, Maica; Malmusi, Davide; Muntaner, Carles; Díez, Elia; Bartoll, Xavier; Borrell, Carme
Abstract : Background: In the last decade, the Neighbourhoods Law in Catalonia (Spain) funded municipalities that presented urban renewal projects within disadvantaged neighbourhoods focusing on physical, social and economic improvements. The objective of the study was to evaluate the effects of this law on the health and health inequalities of residents in the intervened neighbourhoods in the city of Barcelona. Methods: A quasi-experimental predesign and postdesign was used to compare adult residents in five intervened neighbourhoods with eight non-intervened comparison neighbourhoods with similar socioeconomic characteristics. The Barcelona Health Survey was used for studying self-rated and mental health in pre (2001, 2006) and post (2011) years. Poisson regression models stratified by sex were used to compute prevalence ratios comparing 2011 with 2006, and later stratified by social class, to study health inequalities. Results: The intervened neighbourhoods had a significant decrease in poor self-rated health in both sexes while no significant changes occurred in the comparison group. When stratified by social class, a significant improvement was observed in poor self-rated health in the manual group of the intervened neighbourhoods in both sexes, resulting in a decrease in self-rated health inequalities. Similar results were observed in poor mental health of women, while in men, poor mental health worsens in both neighbourhood groups but mostly in the comparison group. Conclusions: The Neighbourhoods Law had a positive effect on self-rated health and seems to prevent poor mental health increases in both sexes and especially among manual social classes.